Tìm hiểu hoạt động tài chính của công ty Xunhasaba trong hai năm 1998 - 1999 : Khóa luận tốt nghiệp - Vũ, Thị Phương Lan (2000)
Tìm hiểu hoạt động tài chính của công ty Xunhasaba trong 2 năm 1998 - 1999.